2003
DOI: 10.1046/j.1365-2427.2003.01149.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of prey morphology on the feeding behaviour and population growth of the predatory rotifer Asplanchna sieboldi: a case study using five species of Brachionus (Rotifera)

Abstract: Summary 1. We investigated the numerical response, functional response and prey preference of Asplanchna sieboldi to five different prey brachionids. We also analysed the feeding behaviour of the predator in terms of encounters, attacks, capture and prey ingested per unit time. 2. The five prey species (Brachionus havanaensis, B. rubens, B. patulus, B. macracanthus and B. calyciflorus) differed in their body size and spine length. 3. The population growth rates of A. sieboldi ranged from 0.074 ± 0.03 to 0.431 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 27 publications
4
29
0
1
Order By: Relevance
“…The effects of prey vulnerability on the functional response and growth have been tested for Asplanchna preying on B. calyciflorus and several other rotifer species (Iyer & Rao, 1996;Nandini et al, 2003). The capture success and ingestion of Asplanchna on spined B. calyciflorus is much lower than on non-spined B. calyciflorus (Iyer & Rao, 1996).…”
Section: Defenses In Herbivorous Rotifersmentioning
confidence: 99%
“…The effects of prey vulnerability on the functional response and growth have been tested for Asplanchna preying on B. calyciflorus and several other rotifer species (Iyer & Rao, 1996;Nandini et al, 2003). The capture success and ingestion of Asplanchna on spined B. calyciflorus is much lower than on non-spined B. calyciflorus (Iyer & Rao, 1996).…”
Section: Defenses In Herbivorous Rotifersmentioning
confidence: 99%
“…in our study Macrothrix showed the highest probability of being killed after an encounter with Hydra (K/e=0.84). it has been observed that prey species with elongated spines such as Brachionus havanaensis and Brachionus macracanthus offer protection against predation by the predatory rotifer Asplanchna because it cannot ingest them (Nandini et al, 2003). in this work, Macrothrix was easily ingested by Hydra, probably because cnidarians possess flexible tissues so that the spines of the prey do not damage them (anderson, 2001).…”
Section: Discussionmentioning
confidence: 65%
“…The r values in population growth studies of A. sieboldi Leydig fed B. havanaensis, B. rubens Ehrenberg, B. patulus Muller, B. macracanthus Jakubski or B. calyciflorus and A. brightwelli fed B. calyciflorus or A. fissa increased with increasing prey density (Sarma et al, 1998(Sarma et al, , 2002bNandini et al, 2003). Similarly, in the present study, at 28 xC, the population growth rate of A. brightwelli increased with increasing B. angularis density.…”
Section: Discussionmentioning
confidence: 99%
“…Most herbivorous rotifers usually have r values about 0.5 day x1 (Sarma et al, 2001), but carnivorous genus may have r values higher than 0.5 up to 1.5 day x1 . The r values of A. girodi ranged from 0.09 to 1.51 day x1 (Dumont and Sarma, 1995;Sarma et al, 2003), and those of A. sieboldi ranged from 0.07 to 0.43 day x1 (Sarma et al, 2002a;Nandini et al, 2003). A. brightwelli had r values of 0.22-1.01 day x1 (Sarma et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation